Efeito agudo das atividades condicionantes exercício de força baseado em velocidade e exercício de força tradicional com uma e duas séries no desempenho do salto vertical - Luna, Yasmim Kéllen Siqueira (2024)
This study compared the effects of conditioning activities, velocity-based strength exercise, and traditional strength exercise with one and two sets on countermovement jump performance in individuals with different strength levels. Seventeen trained men participated (23.53 ± 3.10 years; 1.77 ± 0.07 meters in height; 78.78 ± 7.54 kg; 14.33 ± 4.0% body fat; 7.71 ± 4.38 years of sports experience; 3.94 ± 3.52 years of strength training experience; 144.59 ± 16.51 kg in the 1RM test). Nine sessions were conducted, with the last five dedicated to the experimental conditions: one or two sets of squats at 60% of 1RM until 10% velocity loss, or 85% of 1RM (3 repetitions), in addition to a control condition. Jump height was measured before and after each experimental condition for analysis. A self-selected recovery period was adopted between the conditioning activities and the specific activity for each volunteer. All data were presented as mean and standard deviation (M ± SD). Repeated measures ANOVA showed significant differences in vertical jump performance between the experimental conditions of velocity-based strength exercise with 1 set (VBSE1x) and traditional strength exercise with 2 sets (TSE2x), as well as in absolute and relative deltas, with VBSE1x being the conditioning activity that resulted in better jump performance. When data distribution was not normal, the Friedman test was used. In grouping analyses (strong individuals versus weak individuals, based on the relative 1RM median), no significant differences were observed in any variable. However, individual analyses showed that thirteen of the seventeen participants (76.5%) improved vertical jump performance after VBSE1x. Therefore, using one set of velocity-based strength exercise with moderate load in young, experienced strength trainees resulted in a positive effect on countermovement jump performance. It is also concluded that, although participants' strength levels did not significantly impact the results, this is an important aspect to consider when planning training loads, aiming for a better stimulus-recovery-adaptation relationship.